Effect of the FIFA 11+ programme on vertical jump performance in elite male youth soccer players - Akbari, H.; Sahebozamani, M.; Daneshjoo, A.; Amiri-Khorasani, M. (Montenegrin Journal of Sports Science and Medicine, 2018)
Despite the success of the FIFA 11+ programme in preventing injury, convincing coaches and players to do these exercises is difficult only in order to prevent injury, unless the programme can be shown to have a positive and direct impact on the performance. This study aims to investigate the effect of the FIFA 11+ programme on vertical jump performance in male elite-youth soccer players. Twenty-four male soccer players (mean ± SD: age = 16.79 ± 1.18 years, height = 174.17 ± 8.12 cm, mass = 62.45 ± 10.01 kg, experience = 6.96 ± 1.26 years) participated in this study and were randomly divided equally into two groups, FIFA 11+ and control. The experimental group performed the FIFA 11+ programme three times per week for eight weeks whereas the control group just performed their regular warm-up programme. The mixed-repeated measures ANOVA showed that there was a significant improvement in the vertical jump performance between groups in post-test (P=0.002) while no significant improvement was found between groups after 1-month of stopping the FIFA 11+ programme (P=0.076). It can be concluded that performing the eight-week FIFA 11+ programme can enhance the jump height in male elite youth soccer players. It seems that the FIFA 11+ programme could be incorporated into regular soccer practice as a warm-up programme instead of a conventional warm-up programme. However, due to the failure to maintain the long-term effectiveness of the FIFA 11+ programme on the jump height of soccer players, the continuation of performing this programme is necessary.